Kiai dan Kemandirian Ekonomi Pesantren - Mohammad Anas (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2020)
This is a field research that focuses on pesantren as the oldest and original educational institution in Indonesia and has successfully emerged as an independent educational institution. This success cannot be separated from the work and contribution of the kiai in organizing the pesantren. To unravel this theme, there are two formulations of problems that to be discussed, namely, (1) how is the kiai's role in establishing economic independence at the Mambaus Sholihin Islamic Boarding School, Gresik? and (2) what factors shape the economic independence of the Mambaus Sholihin Islamic Boarding School in Gresik? The method used in this study is a qualitative research method with two approaches, including: first, qualitative case studies which emphasize the subjective aspects of people's behavior. Second, symbolic interaction that seeks to understand human behavior from the subject's point of view. The results of this study conclude that the kiai's role in the economic activities of the pesantren is very significant, both because of internal and external factors in shaping the economic independence of the pesantren.